Is energy healing an effective non-pharmacological therapy for improving symptom management of chronic illnesses? A systematic review. (November 2016) - Rao, Angela; Hickman, Louise D.; Sibbritt, David; Newton, Phillip J.; Phillips, Jane L.
Abstract: Background: Emerging evidence suggests that some people living with non-communicable diseases (NCDs) have integrated energy healing into their self-management strategy, however little is known about its efficacy. Purpose: To identify energy healing interventions that impacted positively on the symptom management outcomes for patients living in the community with various NCDs. Methods: A systematic review of energy healing interventions for the management of non-communicable disease related symptoms, conducted between 01 January 2000 and 21 April 2015, published in an English peer-reviewed journal. This review conforms to the PRISMA statement. Results: Twenty seven studies were identified that evaluated various energy healing interventions involving 3159 participants. Thirteen of the energy healing trials generated statistically significant outcomes. Conclusions: Energy healing has demonstrated some improvement in illness symptoms, however high level evidence consistently demonstrating efficacy is lacking. Further more robust trials are required to better understand which elements of energy healing interventions are associated with positive outcomes.